Study on river water treatment by photocatalysis using metal-modified titania nanotubes. Issue 1 (1st October 2022) - Thuy, Nguyen Thi; Diem Ngoc, Vo Tran; Cam Tien, Nguyen Thi; Thanh, Dang Van; Thanh, Nguyen Trung; Khoi, Tran Tien; Huy, Nguyen Nhat
Abstract: This study aimed to treat river water for domestic water supply purposes in the South of Vietnam by photocatalysis. Since the pre-treatment of traditional coagulation was effective in removing turbidity and other pollutants, the photocatalytic step was mainly applied for the removal of organics and disinfection of pathogens. The titanium nanotubes (TNTs) was synthesized by hydrothermal method using Degussa P25 precursor and the TNTs was then impregnated with 12 metal salts (i.e., MgCl2, ZnSO4, SnCl2, MnSO4, Fe(NO3 )3, Cu(NO3 )2, and Ni(NO3 )2, Al(NO3 )3, CrCl3, Cd(NO3 )2, Sr(NO3 )2, and Co(NO3 )2 ) under various molar ratios and different heating temperatures. Among these materials, the TNTs modified with Ni(NO3 )2 solution provided the best organics and Coliforms treatment. Operating conditions of the photocatalytic process such as light irradiation, catalytic dosage, pH, and water sources affecting the pollutant treatment efficiency were evaluated. The results showed that TNTs which was prepared at pH 1.6, impregnated with Ni(NO3 )2 at 1% molar ratio, and calcined at 400°C for 2 hours were able to treat organic contents at 83.33% removal efficiency and completely removed Coliforms under UVA irradiation for 20 min. We hence suggest this material as a promising photocatalyst for organic content removal and disinfection of surface water for drinking water supply.